Peran Budaya Upacara Adat Kawin-Mawin Dalam Menjaga Kerekatan Hubungan Sosial Masyarakat Desa Umbu Ma-mijuk-Ntt (Studi Deskriptif Analisis Terhadap Peran Nilai Sosial Pendidikan Ips) - Lelung; Rikardo Umbu Daku; Onik Farida. N (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
This research describes: (1) How is the process of implementing the traditional kawin-mawin ceremony for the community of Umbu Mamijuk village, Central Sumba-NTT, (2) What is the form of community social relations in the implementation of the traditional ceremony of marriage-mawin for the community of Umbu Mamijuk village, Central Sumba-NTT, (3) What values ​​are contained in the customary procession of mawin-mawin in maintaining close social relations between the community of Umbu Mamijuk village, Central Sumba-NTT, Ethnographic research method with anthropological form. The research location, Umbu Mamijuk village, Central Sumba District-NTT. Types of qualitative data, primary and secondary data sources. The research instruments included observation, interviews, and direct observation of the field. Data collection techniques using: (1) observation, (2) interviews and (3) documentation. Data analysis used interactive analysis through problem formulation, data collection, data reduction, data presentation, and conclusion drawing. The validity of the research data used source triangulation, audit trail, debiting, member check, and extension of observations. The results of the research: (1) the process of the traditional ceremony of kawin-mawin for the people of the village of umbu mamijuk, Central Sumba-NTT has four stages that must be followed: (a) knocking the door / halatung marada, (b) ngidi pamama, (c) dadang nulang lunu tapu which combined the third and fourth stages together. (2) the form of social relations in the form of mutual assistance and respect between fellow communities in the customary process, (3) the social values ​​contained, namely the value of mutual cooperation and mutual respect.